The economic circumstances of cohorts born between the 1940s and the 1970s - Andrew Hood; Robert Joyce (Institute for Fiscal Studies (IFS), 2013)
This report compares and contrasts the economic circumstances of individuals born between the 1940s and the 1970s, currently ages between their mid-30s and mid-70s. In doing so, it aims to provide a sense of the likely economic position of the younger cohorts in later life, in absolute terms and relative to their predecessors. The main conclusion is that individuals born in the 1960s and 1970s are likely to be reliant on inherited wealth if they are to be any better off in retirement than their predecessors. When compared with those born a decade earlier at the same age, these cohorts have no higher take-home income; have saved no more previous take-home income; are less likely to own a home; are likely to have lower private pension wealth; and will tend to find that their state pensions replace a smaller proportion of prior earnings. Many more people in younger cohorts expect to inherit wealth; but expected inheritances are distributed unequally and are higher for those who are already wealthier.
Keywords: 330